2009
DOI: 10.1111/j.1540-8167.2008.01319.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Chronaxies for Ventricular Fibrillation Induction, Defibrillation, and Cardiac Stimulation: Unexpected Findings and Their Implications

Abstract: It may be reasonable to study whether LEC pulses from 0.25 ms to 0.30 ms in duration and up to 250 V in amplitude would increase therapeutic yield in VT termination without VF induction in humans. Contrary to the current belief, the discrepancy between defibrillation and stimulation chronaxie is not caused by different electrode size. We postulate that the time constant of the fast sodium channel reactivation may be the underlying reason.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
(171 reference statements)
1
12
0
Order By: Relevance
“…A table of optimal pulse durations under the assumption of a chronaxie of 2 ms can be found in the above‐mentioned paper . Some studies have reported larger chronaxie values, but they considered the rheobase as a lower limit for the average current and not for the instantaneous current (or field) The rheobase field for myocardial cells is of the order of 60 V/m .…”
Section: Discussionmentioning
confidence: 99%
“…A table of optimal pulse durations under the assumption of a chronaxie of 2 ms can be found in the above‐mentioned paper . Some studies have reported larger chronaxie values, but they considered the rheobase as a lower limit for the average current and not for the instantaneous current (or field) The rheobase field for myocardial cells is of the order of 60 V/m .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal , Lawo et al 47 . show experimental evidence that suggests that strength–duration curve may offer additional insights that seem to have been overlooked so far by old theories.…”
Section: Editorial Commentmentioning
confidence: 99%
“…Strength-duration curves were theoretically studied for optimizing ventricular defibrillation thresholds for both square-wave stimulation pulses and exponential discharge pulses and were shown to be ideally hyperbolic (Irnich 2008;Koning et al 1975). Experimental studies of strength-duration relationships were conducted, e.g., in the left ventricular epicardium of patients undergoing cardiac resynchronization therapy (Dhar et al 2009;Scally et al 2007), in the right ventricular apex for transvenous defibrillation in humans and in animal models, as well as in the atria and ventricles of patients with acutely implanted pacing leads (Coates and Thwaites 2000;Gold and Shorofsky 1997;Lawo et al 2009). …”
Section: Introductionmentioning
confidence: 98%